Mineral density of bone tissue in women with arthrosis of various locations - Korzh, Mykola; Yakovenchuk, Natalia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Arthrosis and osteoporosis — common diseases of the musculoskeletal system in the elderly, precocious and senile age, which predetermines the study of their general pathogenetic mechanisms of development. Objective: to study the bone mineral density in women with various clinical forms of arthrosis. Methods: bone mineral density was analyzed in 282 patients over 56 years of age with gonarthrosis, coxarthrosis and spondyloarthrosis. The examined groups of patients did not differ by body mass index and age. The bone mineral density study was performed on the bone densitometer «Explorer QDR W» (Hologic) in the lumbar spine, proximal femoral area, with an additional assessment of the femoral neck or distal posterior part of the forearm. The diagnosis of «osteopenia» or «osteoporosis» was established in accordance with WHO recommendations fand using t-criterion. Digital figures were statistically calculated using the Excel 2003 program. Results: after analyzing the densitometric measurements of bone mineral density in patients with various clinical forms of arthrosis, the lowest rates were observed in women with coxarthrosis (80.4 %) and spondylarthrosis (71.4 %). In patients with gonarthrosis, bone mineral density rates were reduced by 57.2 %. Osteoporosis was found in 26.1 % of women with gonorrhea, 25.5 % with coxarthrosis, and 38.4 % with spondylarthrosis. Significant decrease in bone mineral density was found in the axial part of the skeleton (lumbar spine and femoral neck) in patients with coxarthrosis and gonarthrosis compared to the forearm bones (p < 0.05). In the case of spondylarthrosis, the decrease in bone mineral density is recorded both in the axial and in the peripheral parts of the skeleton. Conclusions: women with different clinical forms of osteoarthritis have low bone mineral density with a prevalence of osteopenia. The obtained data testify to the need for further study of the common pathogenetic mechanisms for the development of reduction of bone mineral density and arthrosis.